A Study on Brand Consciousness Among Children and Its Effect on Family Buying Behaviour in Bangalore City - Vincent, Nithila (Ushus Journal of Business Management, 2007)
Children today are extremely aware of the various brands in the market and are conscious of the products they use or consume. They pick and choose carefully according to their needs, style preference etc. They also exercise a lot of independence in decision-making and influence the family buying behaviour. This study is an attempt to examine the level of brand consciousness among Indian children. Few specific studies on brand consciousness among Indian children have been conducted so far. Further this study also analyses the effect of such brand consciousness in children on the family buying behaviour. This study is based on the findings of a survey of 222 children and 222 parents spread over the south of Bangalore City. The children were in the age group of 8 to 16 years, both boys and girls selected at random within the age group mentioned, using convenience sampling method without any stratification to obtain a uniform size of respondents in each age / sex category.